Labor market institutions: Curse or blessing? - Carsten Ochsen; Heinz Welsch (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
Previous literature has identified considerable non-pecuniary costs to macroeconomic fluctuation and uncertainty. The present paper investigates whether and to what extent labor market institutions can mitigate those costs. We study how life satisfaction of European citizens is affected by employment protection and the level and duration of unemployment benefit payments. We differentiate between direct effects (at given macroeconomic conditions) and total effects (including the feedback through the institutions' effect on macroeconomic outcomes). We find that the total effect of employment protection is positive, whereas the total effect of benefit duration is negative. The direct and indirect effects of a higher benefit level nearly neutralize each other.
Keywords: J30; E24; E60; D71; I31; 330; unemployment benefit; employment protection; macroeconomic uncertainty; cost-benefit analysis; life satisfaction; happiness